(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The present study was designed to conduct the comparative study ofeffects of Physical, Exercise, on selected physiological variables amongSecondary school boys of Bhiwani district of Haryana, those who participated atinter university level event in Kurukshetra University, Kurukshetra and CDLU,Sirsa. The present chapter divided into two parts. viz. Analysis of data anddiscussion of finding.